2004
DOI: 10.4049/jimmunol.172.6.3719
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Helper Response Rescues Otherwise Low Avidity CD8+ Memory CTLs to Become Efficient Effectors In Vivo

Abstract: This report seeks a means of maximizing memory CD8 T cell responses to peptide immunization. Delivery of the CD8 peptide epitope by stress protein, heat shock protein (hsp)70, results in excellent immunogenicity at the acute phase but memory responses were poor both in terms of the number of responding cells as well as their functional avidity. We demonstrate for the first time that hsp70 can also be used as a vehicle to achieve CD4 T cell responses to loaded peptide epitopes and that coimmunization with hsp70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…IL-12 enhances Th1 cell polarization, leading to more IFNγ and TNFα production. Through these cytokines, Th1 cells synergize with CTL and DC in anti-tumor immunity [4][5][6][7][8][9]. We have shown previously that immunization with attenuated activated autologous T cells leads to more IL-12 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-12 enhances Th1 cell polarization, leading to more IFNγ and TNFα production. Through these cytokines, Th1 cells synergize with CTL and DC in anti-tumor immunity [4][5][6][7][8][9]. We have shown previously that immunization with attenuated activated autologous T cells leads to more IL-12 production.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that activity of Th1 cells is downregulated in patients with malignant tumors. For example, tumor patients had lower concentrations of Th1 cytokines in serum, which may lead to low CTLmediated anti-tumor activity and dampened DC function [9][10][11]. Treating patients with IL-2 plus IFNγ may induce tumor regression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo cytolytic activity was determined as described previously (18). Briefly, splenocytes from C57BL/6 mice were stained with PKH26 (PKH26-GL; Sigma-Aldrich) or 1.5, 0.15, or 0.03 M CFSE.…”
Section: In Vivo Cytotoxicity Assaymentioning
confidence: 99%
“…To evaluate the functional avidities of the effector populations further, we performed an in vivo CTL assay (18). Differentially CFSE-labeled splenocytes from naive syngeneic mice were pulsed with varying concentrations of SIINFEKL peptide (100, 10, or 1 nM) and i.v.…”
Section: Effector T Cells Induced By Pdom-sl8 Vaccination Are Functiomentioning
confidence: 99%
“…27 It is now firmly established that for robust and persistent CD8 þ T-cell responses a concomitant CD4 þ T-helper response is needed. [28][29][30][31] Therefore, HLA class II presented tumor-specific epitopes are preferably incorporated in peptide vaccines to promote the CTL-mediated tumor destruction.…”
Section: Vaccination Strategies With Defined T-cell Epitope Containinmentioning
confidence: 99%